Tuning conversion efficiency in metallo endohedral fullerene-based organic photovoltaic devices - Ross, Russel B.; Cardona, Claudia M.; Swain, Francis B.; Guldi, Dirk Michael; Sankaranarayanan, Shankara Gayathri; Van Keuren, Edward; Holloway, Brian C.; Drees, Martin (Advanced Functional Materials, 2009)
Here the influence that l-(3-hexoxycarbonyl)propyl-l-phenyl-[6,6]-Lu N@C, LuN@C-PCBH, a novel acceptor material, has on active layer morphology and the performance of organic photovoltaic (OPV) devices using this material is reported. Polymer/fullerene blend films with poly(3-hexylthiophene), P3HT, donor material and Lu N@C-PCBH acceptor material are studied using absorption spectroscopy, grazing incident X-ray diffraction and photocurrent spectra of photovoltaic devices. Due to a smaller molecular orbital offset the OPV devices built with LuN@C-PCBH display increased open circuit voltage over empty cage fullerene acceptors. The photovoltaic performance of these metallo endohedral fullerene blend films is found to be highly impacted by the fullerene loading. The results indicate that the optimized blend ratio in a P3HT matrix differs from a molecular equivalent of an optimized P3HT/ [6,6]-phenyl-C-butyric methyl ester, C-PCBM, active layer, and this is related to the physical differences of the C fullerene. The influence that active layer annealing has on the OPV performance is further evaluated. Through properly matching the film processing and the donor/acceptor ratio, devices with power conversion efficiency greater than 4% are demonstrated. © 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.